2011
DOI: 10.1038/jes.2011.31
|View full text |Cite
|
Sign up to set email alerts
|

Persistent organic pollutant concentrations in first birth mothers across Mexico

Abstract: This project was initiated by the North America Commission for Environmental Cooperation (CEC). Its main purpose was to obtain an initial profile on pregnant woman's exposure to persistent organic pollutants (POPs) in North America (Canada, the United States and Mexico). Persistent organic pollutants are transferred to the fetus via the placenta during the pregnancy or to the infant via maternal milk; therefore, the pregnant woman's body burden is important because of the higher exposures and potential health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
0
15
0
1
Order By: Relevance
“…Two recent papers have reported the analysis of data from this CEC study for Canada (Foster et al, 2012) and Mexico (Rodriguez-Dozal et al, 2012). In each case the analysis was restricted to comparisons between sites or regions within each country.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Two recent papers have reported the analysis of data from this CEC study for Canada (Foster et al, 2012) and Mexico (Rodriguez-Dozal et al, 2012). In each case the analysis was restricted to comparisons between sites or regions within each country.…”
Section: Discussionmentioning
confidence: 99%
“…The Canadian analysis by Foster et al (2012) focused on concentrations of POPs and metals in primiparous women and found statistical differences between the 5 Canadian sites for several contaminants after adjusting for age and BMI, although no one site was consistently higher for all contaminants. The paper by Rodriguez-Dozal et al (2012) did not look at concentrations of metals, but instead focused on POPs and pooled samples of di-oxins, furans and dioxin-like PCBs in primiparous women. Significant differences were observed for several contaminants between the 10 Mexican study sites and concentrations of some POPs at certain sites were higher than originally expected based on the hypothesized exposure scenario (Rodriguez-Dozal et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Madres embarazadas residentes de Veracruz presentaron concentraciones de DDE y DDT en suero sanguíneo en niveles que variaron desde concentraciones por debajo del límite de detección del método a 0.98 µg/g y de 0.24 a 20.85 µg/g, respectivamente (Waliszewski et al 2000). Rodríguez-Dozal et al (2012) cuantificaron el DDE en plasma sanguíneo de madres que habitaban zonas urbanas del país (Querétaro, Tultitlán, Mérida, Salamanca, Monterrey, Guadalajara, Hermosillo, Córdoba, Coatzacoalcos y Cd. Obregón).…”
Section: Exposición En Mujeres En Edad Reproductivaunclassified